Frequency domain model for zero-sequence electromagnetic harmonic filter performance analysis - Oliveira, Jose C.; Oliveira, Luis C. O.; Belchior, Fernando N. [UNESP]; Oliveira, Rodrigo N.; Barbosa, Joao Areis F. (Wiley-Blackwell, 2015)
Using frequency domain approach, this paper focuses on a zero-sequence harmonic filter model. The model is based on electromagnetic arrangement created through a three-legged core construction and zigzag windings that provide a low-priced, robust and efficient equipment to reduce zero-sequence fundamental and harmonic distortion. The methodology adopted here provides a useful technique for evaluating the steady-state operation of the filter with emphasis on its efficiency at reducing harmonics and at identifying the main constructive and electrical parameters of influence on the product performance. The representation is based on sequence harmonic transmittances that were found helpful in estimating the filter operational characteristics under both ideal and non-ideal conditions. Furthermore, the effectiveness of the filter and its representation are fully validated using an equipment prototype and laboratory results. Copyright (c) 2014 John Wiley & Sons, Ltd.
Keywords: frequency domain model; electromagnetic device; harmonics filters; zero-sequence current; power quality